Diagnostic Performance between Histidine-Rich Protein 2 (HRP-2), a Rapid Malaria Diagnostic Test and Microscopic-Based Staining Techniques for Diagnosis of Malaria - Jean Baptiste Niyibizi; Emmanuel Kamana Gatera (Journal of Tropical Medicine)
Malaria presents a diagnostic challenge in most tropical countries such as Rwanda. Microscopy remains the gold standard for diagnosing malaria, but it is labor intensive and depends upon the skill of the examiner. Malaria rapid diagnostic tests (RDTs) have been developed as an easy, convenient alternative to microscopy. This cross-sectional study was conducted at Rukara Health Center which is located in Eastern Province, Kayonza district, Rwanda. One hundred and fifty suspected cases of malaria, who attended Rukara Health Centre, during the period, from 21st June to 30th July 2018, were included in this study. HRP-2 RDTs (CareStart™ Malaria HRP-2 (Access Bio, Inc., Somerset, New Jersey, USA)), for malaria were performed. Thick smears were prepared and Giemsa-stained as recommended; then slides were observed under microscopy and reported quantitatively; RDTs were reported qualitatively (positive or negative). Both RDTs and thick smear results were recorded on data collection sheet. This study included a total of 150 study participants, 87 (58%) females and 63 (42%) males. The patients included in the study did not receive any antimalarial drug. The mean age of the study participants was 31.6 ± 12.4 with the majority of participants being between 25 and 44 years and the minority being above 65 years. The sensitivity of RDT (HRP-2) was calculated and found to be 95.0%, whereas the sensitivity of Giemsa microscopy was 100%. The specificity of RDT (HRP-2) was calculated and found to be 59.2%, whereas the specificity of Giemsa microscopy was 100%. Negative and positive predictive values of RDT are 85.4% and 82.7%, respectively. Negative and positive predictive values of Giemsa microscopy were both 100%. According to the results of the current study, the sensitivity, specificity, and both positive and negative predictive values of Giemsa microscopy are higher than those of histidine-rich protein 2-based rapid diagnostic test for malaria. The results obtained in histidine-rich protein 2-based rapid diagnostic test for malaria parasites should be confirmed with tests with high specificity. Further studies should determine the most appropriate type of rapid diagnostic test of malaria diagnosis to be used in combination with Giemsa microscopy. In addition, sensitivity and specificity of RDT (HRP-2) and Giemsa microscopy should be assessed against molecular biology techniques.